Network Security Analysis Using Switch Port Security CPT - Istiqamah, Nurfadilah; Parenreng, Jumadi Mabe (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2023)
The gradual advancement of information network technology has rapidly increased due to the growing demand for efficient, stable, and fast network connectivity, as well as reliable information security. One factor that influences network quality is network security, which encompasses various techniques to enhance network security, such as building firewalls, layer seven protocols, and port security. Port security utilizes existing ports to enable secure switching access. The switch can protect the local area network (LAN). Several types of switch port security are commonly used, including default/static port security, dynamic learning port security, and sticky port security.